THE MEDIA AND SOCIO-POLITICAL CHANGE: A SNAPSHOT OF NORTH AFRICA AND GHANA’S CASE (Paramita: Historical Studies Journal, 2019)
The mass media is a very useful tool to educate, to inform and to entertain. However, recent studies have shown that the media in whatever form has contributed immensely to bring about both social and political change in respective communities across the globe and Africa in particular. The case of Ghana has been presented from the different tangents by different authors. Significantly, this contribution pays attention to the role of the press (media) as well as the digital media in ensuring effective social and political change. In the first instance, this looks at the role of the media from the past to present and juxtaposes that with recent developments in Ghana and other African Countries. Attention is also paid to the role of the media in the respective elections in Ghana.Keywords: Press, Mass Media, Politics, Democracy, Transitions, Political Development, Social Development Media massa adalah alat yang sangat berguna untuk mendidik, menginformasikan, dan menghibur. Namun, penelitian terbaru menunjukkan bahwa media dalam bentuk apa pun telah berkontribusi besar untuk membawa perubahan sosial dan politik di komunitas masing-masing di seluruh dunia dan Afrika pada khususnya. Kasus Ghana telah disajikan dari berbagai garis singgung oleh penulis yang berbeda. Secara signifikan, kontribusi ini memperhatikan peran pers (media) serta media digital dalam memastikan perubahan sosial dan politik yang efektif. Dalam contoh pertama, ini terlihat pada peran media dari masa lalu hingga sekarang dan menyandingkan bahwa dengan perkembangan terakhir di Ghana dan negara-negara Afrika lainnya. Perhatian juga diberikan pada peran media dalam pemilihan masing-masing di Ghana.Kata kunci: Pers, Media Massa, Politik,   Demokrasi, Transisi, Perkembangan Politik, Pembangunan Sosial